1972
DOI: 10.1530/jrf.0.0300309
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization in Vitro of Mouse and Hamster Eggs After the Removal of Follicular Cells

Abstract: Summary. The removal of follicular cells decreased the proportion of mouse eggs penetrated by epididymal spermatozoa, but did not affect the proportion of hamster eggs penetrated, whether the spermatozoa were taken from the epididymis or from the uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

1974
1974
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 13 publications
(19 reference statements)
1
18
1
1
Order By: Relevance
“…The Gordon HYDothesis (Gordon, 1973: Gordon et al, 1978 Gordon hypothesizes that the removal of a seminal plasma factor activates a calcium independent ATPase in the sperrn plasma membrane. This ATPase then transports extracellular Ca 2 + into the space between the outer acrosomal and plasma Miyamoto and Chang, 1972). In addition, as was mentioned earlier, Moore and Bedford (1978) have reported that fertilization of washed ova can occur in vivo and in vitro in the absence of follicular products.…”
Section: Folllcular Fwid and The Oviductmentioning
confidence: 79%
“…The Gordon HYDothesis (Gordon, 1973: Gordon et al, 1978 Gordon hypothesizes that the removal of a seminal plasma factor activates a calcium independent ATPase in the sperrn plasma membrane. This ATPase then transports extracellular Ca 2 + into the space between the outer acrosomal and plasma Miyamoto and Chang, 1972). In addition, as was mentioned earlier, Moore and Bedford (1978) have reported that fertilization of washed ova can occur in vivo and in vitro in the absence of follicular products.…”
Section: Folllcular Fwid and The Oviductmentioning
confidence: 79%
“…The role of cumulus components for the capacitation of hamster spermatozoa and penetration of hamster eggs has been reported by Gwatkin et al (1972), but Miyamoto & Chang (1972) observed that there was no difference in the penetration rates (91 versus 87 %) of hamster eggs with or without follicular cells incubated with epididymal spermatozoa in an equal volume of Tyrode's solution and heated hamster blood serum. Since only 4% of denuded hamster eggs were penetrated in the rabbit medium which contained BSA (Table 2), the heated hamster blood serum may play an important role for the capacitation and acrosome reaction of hamster spermatozoa in the absence of follicular cells.…”
Section: Effect Of Bsa Andpvpmentioning
confidence: 83%
“…or for the rabbit (Brackett, 1970) showed that rabbit medium was superior to the rat medium but that the penetration rates were still quite low (12-36%, Table 1). Although hamster eggs can be fertilized in a modified Tyrode's solution containing BSA without any biological fluid (Bavister, 1969(Bavister, , 1973, high penetration rates occur in Tyrode's solution containing follicular fluids (Yana¬ gimachi, 1969a, b), or blood serum (Yanagimachi, 1970;Miyamoto & Chang, 1972,1973Miyamoto et al, 1974). It appears, therefore, that a particular medium is best for a given species and that a medium with biological fluid may be better than one without.…”
Section: Effect Of Bsa Andpvpmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was reported by Hanada & Chang (1976) (Brackett, 1970) or rat eggs (Toyoda & Chang, 1974), much higher penetration rates occur in Tyrode's solution and modified Medium 199 containing follicular fluids (Barros & Austin, 1967;Yanagimachi, 1969a, b;Gwatkin & Andersen, 1969) or blood serum (Yanagimachi, 1970;Miyamoto & Chang, 1972b). Gwatkin, Andersen & Hutchinson (1972) reported that the cumulus components play an important role in the capacitation of spermatozoa and fertilization of hamster eggs in vitro.…”
Section: Introductionmentioning
confidence: 96%